AKUNTANSI DAN AKUNTAN DALAM PERSPEKTIF ISLAM - Maryatin Maryatin; Muhammad Nur Salim (Universitas Muhammadiyah Kudus, 2024)
This article examines accounting can be called art, science or technology if viewed philosophically. From there, Islam will be right to place its Perspective. Accounting if it is a science with Accounting if it is a technology is from the perspective that Accounting is an applied science, and technology is the intended applied science. This article is the result of qualitative research by conducting a literature study. The presentation and management of data is carried out using descriptive-analytical methods, thus this article attempts to present problems according to their reality, then an in-depth analysis is carried out on data and facts that are library-based so that an explanation is obtained about Accountants and accountants with all their criteria. Accounting is not a science, because accounting does not have the characteristics of science. But technology is closer to the term Accounting, the follow-up is that the knowledge tools in accounting must be developed with technological characteristics so that they can be more useful and have a real influence on social life. Islam is used as a rule or guideline when an Accountant carries out his professional work, both when recording, measuring, analyzing, presenting reports, and in analyzing events or incidents. Based on the research results and discussions and conclusions, several suggestions that can be conveyed by the research are to expand the scope of the sample and the scope of the object that is expanded for further research